A new lightweight partition made with cork and gypsum board - António P. O. Carvalho (1996)
The purpose of this paper is to present an indigenous material (cork) in an innovative design approach for housing. The building construction development in Portugal has been changed by the very slow but gradual move to a general use of partitions made with increasingly light materials from the traditional heavy interior walls. A socioeconomic analysis of the Portuguese situation as it is concerned with the lodging policies and building construction industry, is briefly presented and confronted to 37 other countries. An international comparison on this matter is shown using some economic parameters. The main goal of this paper is to present a study of the acoustical behavior of lightweight partitions, especially those usually called sandwich-type and its experimental application to a new and very specific kind of partition made of gypsum board and cork, a traditional material in Portugal. This newly developed sandwich lightweight partition is presented and acoustically characterized. A new and simple mathematical model is presented to evaluate the sound isolation of this kind of partition. The results obtained in reverberant chamber tests are presented as well as the comparisons with the predicted values using the new model proposed. Different single and double wall types were tested giving STC values up to 44 dB.